Responding to TESOL’s 6 Principles for Exemplary Teaching of Young English Learners: Review of Recent Research in Serbia - Savić, Vera M. (Studies in Teaching and Education, 2025)
Teaching English as a foreign or additional language (L2) at ever-younger ages has become a growing trend in the 21st century. Given the rapidly changing world and technology development, early language learning (ELL) and teaching has experienced a significant paradigm shift that highlights postmethod pedagogy, multilingualism, multiliteracies, whole-child approach, integrated curriculum, intercultural communication, and the implementation of a number of innovative approaches that can prepare children to thrive as global citizens in an uncertain future. The aim of the study was to determine how well the Serbian L2 context had responded to the paradigm shift. We reviewed recent ELL research in Serbia, and mapped the results onto the framework of TESOL Association’s The 6 Principles for Exemplary Teaching of English Learners (The 6 Principles), the most comprehensive global guidelines for bridging the gap between the challenges posed by the new paradigm and high-quality L2 education. Our survey dataset comprised 29 empirical studies, written in English and published in the last 10 years. The findings indicated that all studies were embedded in a theory, dealt with L2 learning in pre-primary (2 studies) and primary contexts (27 studies), a majority focusing on teacher perspectives and competencies, a minority investigating learner skills and perspectives, and only two studies examining both teachers’ and learners’ views. Our meta-study showed that The 6 Principles’ requirements had partly been met in ELL and teaching in Serbia, but it also pointed to some huge steps already made in that direction. Implications for future studies are suggested.